The relationship between gadget usage and the mental emotional state of schoolchildren during the COVID-19 pandemic - Lee, Siew Pien (IIUM Press, 2023)
Introduction: The COVID‑19 pandemic and associated public health measures have disrupted the mental health or well-being of children in some way. It is already evident that the increased use of gadgets and excessive screen time during the COVID-19 pandemic among children and adolescents has a significant influence on mental and emotional well-being among children. Objective: This study aimed to determine the association between device usage and the mentalemotional state of schoolchildren during the COVID-19 pandemic. Methods: This is a quantitative cross-sectional study. A questionnaire survey was employed using the Malay Parent-Report Version of the Strengths and Difficulties Questionnaire, conducted among 232 parents of schoolchildren aged 7 to 12 years. Descriptive and inferential statistics were used to draw insights from the data. Results: The findings indicate a statistically significant relationship between gadget usage (including the duration of playing a gadget per day, the frequency of playing a gadget per week, the type of gadget, ownership of the gadget, and the use of a gadget) and mental emotional state among schoolchildren (p value ˂ 0.05). Conclusion: The outcomes of the study indicate that the pattern of electronic gadget usage has significantly impacted schoolchildren's mental and emotional states.